2018
DOI: 10.3390/rs10081316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Five Satellite-Based Precipitation Products in Two Gauge-Scarce Basins on the Tibetan Plateau

Abstract: Abstract:The sparse rain gauge networks over the Tibetan Plateau (TP) cause challenges for hydrological studies and applications. Satellite-based precipitation datasets have the potential to overcome the issues of data scarcity caused by sparse rain gauges. However, large uncertainties usually exist in these precipitation datasets, particularly in complex orographic areas, such as the TP. The accuracy of these precipitation products needs to be evaluated before being practically applied. In this study, five (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 76 publications
5
61
0
Order By: Relevance
“…Apparently, the CPC model reduced its corresponding ET by using a higher ESCO parameter, so that the lack of precipitation inputs would be offset by less evaporation. This result is consistent with that reported by Bai & Liu (2018), who conducted a study at the source regions of the Yellow River and Yangtze River basins in the Tibetan Plateau. They further concluded that the impact of different precipitation inputs on runoff simulation is largely offset by parameter calibration, resulting in significant differences in evaporation and storage estimates.…”
Section: Effect Of Opps Difference On Hydrological Process Simulationsupporting
confidence: 93%
See 1 more Smart Citation
“…Apparently, the CPC model reduced its corresponding ET by using a higher ESCO parameter, so that the lack of precipitation inputs would be offset by less evaporation. This result is consistent with that reported by Bai & Liu (2018), who conducted a study at the source regions of the Yellow River and Yangtze River basins in the Tibetan Plateau. They further concluded that the impact of different precipitation inputs on runoff simulation is largely offset by parameter calibration, resulting in significant differences in evaporation and storage estimates.…”
Section: Effect Of Opps Difference On Hydrological Process Simulationsupporting
confidence: 93%
“…Thus, this fundamental issue must be addressed before hydrologic modeling with open-access precipitation datasets can be utilized at maximum capacity; as without a thorough understanding of the water cycle's inner processes, the hydrologic models may be highly misleading and facilitate inappropriate management decisions. Bai & Liu (2018) used an HIMS model to simulate the runoff driven by CHIRPS, CMORPH, PERSIANN-CDR, TMPA 3B42, and MSWEP at the source regions of the Yellow River and Yangtze River basins in the Tibetan Plateau. They reported that parameter calibration significantly counterbalanced the impact of diverse precipitation inputs on runoff modeling, resulting in substantial differences in evaporation and storage estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Bai and Liu [48] evaluated CMORPH, TMPA, MSWEP, and a few other SPPs over the complex terrain of the Tibetan Plateau and concluded that MSWEP generally provides the best validation results. The authors noted, however, that since MSWEP directly incorporates global-scale daily gauge data, evaluation of this product using the rain gauges could raise independence issues.…”
Section: Discussionmentioning
confidence: 99%
“…The PERSIANN-CDR product was developed by the organization, which is Center for Hydrometeorology and Remote Sensing of the University of California (USA), using an artificial neural network model in combination with an algorithm for the classification of meteorological elements [34]. It constitutes a daily precipitation data with 0.25 • spatial resolution for the region 60 • S-60 • N over the quasi-global range from 1983 to the present [35]. It can be used for long-term (>30 years) precipitation assessment and drought monitoring and investigation of other extreme events attributable to climate change.…”
Section: Satellite Precipitation Productsmentioning
confidence: 99%